PENERAPAN PENDEKATAN PEMBELAJARAN PAKEM DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 002 BAGAN BESAR - Elvi Zahara (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research was the low mathematics learning outcomes of students. This condition was caused by the teaching of mathematics, which tended to be boring, monotonous, stressful, and less meaningful. Based on the problems encountered in the field, particularly in grade IV at SDN 002 Bagan Besar, it was necessary to implement a learning strategy that could create active, creative, effective, and enjoyable mathematics learning. This study was a Classroom Action Research (CAR). The data collection instruments used were observation sheets and learning outcome tests. The results showed a significant increase in students’ activities from the first cycle to the second cycle. The improvement in active, creative, effective, and enjoyable learning was followed by an increase in students’ learning outcomes. This was evidenced by the improvement in learning outcomes from the first cycle to the second cycle, where the average score increased from 88.27 in Cycle I to 97.59 in Cycle II.